Behavioural mHealth in developing countries: What about culture? / Andre Matthias Müller - Müller, A.M. (European Health Psychology Society, 2016)
Behavioural health in many developing countries (Lachat et al., 2013) one could suggest to simply make use of infrastructure that is already available – the mobile technology infrastructure. This seems sensible considering that modern mobile technology has reached almost every person on our planet. Additionally, the digital divide between developed and developing countries is closing and in 2016 95% of the global population has access to a mobile phone network while the number of mobile broadband subscriptions grows rapidly especially in developing countries (International Telecommunication Union, 2016). Mobile technology ownership is also not limited to any specific demographic because it is increasingly affordable and hence, there is potential to utilise behavioural mHealth approaches to successfully deal with NCDs in developing countries (Beratarrechea et al., 2014; Stephani, Opoku, & Quentin, 2016).